"Incidencia del liderazgo pedagógico en la implementación de un programa de educación socioemocional en los niños de Subnivel Básica Elemental de la Escuela de "Carlos Montúfar de la parroquia El Lucero, cantón Calvas, provincia de Loja, en el periodo lectivo 2024 - 2025" - Chamba Briceño, Rosa Alexandra (2025)
The purpose of this research is to analyze "The impact of pedagogical leadership on the implementation of a socio-emotional education program for children in the Elementary Basic Sublevel at 'Carlos Montúfar' School, located in El Lucero parish, Calvas canton, Loja province, during the 2024-2025 school year." To achieve this, the following objectives were proposed:Analyze the impact of pedagogical leadership on the implementation of a socio- emotional education program for children in the Elementary Basic Sublevel at "Carlos Montúfar" School in El Lucero parish, Calvas canton, Loja province, during the 2024-2025 school year.Determine the influence of pedagogical leadership on the effectiveness of a socio- emotional education program for children in the Elementary Basic Sublevel. Identify the pedagogical leadership strategies employed by teachers. Evaluate the level of knowledge that Elementary Basic Sublevel teachers have regarding the potential impact of a socio-emotional education program. This study adopted a quantitative, non-experimental, and correlational approach, utilizing a statistical analysis design to examine the relationship between two variables: pedagogical leadership and the implementation of the socio-emotional education program. The study population consisted of 40 students enrolled in the Elementary Basic Sublevel at the institution and three homeroom teachers. The results revealed that effective leadership not only enhances emotional identification and management but also fosters a conducive educational environment for learning. Therefore, it is crucial for educational leadership to focus on creating guidelines that promote comprehensive emotional education, engaging all stakeholders in the educational process.